1994
DOI: 10.1111/j.1550-7408.1994.tb01523.x
|View full text |Cite
|
Sign up to set email alerts
|

The Journey of Malaria Sporozoites in the Mosquito Salivary Gland

Abstract: The life cycle of malaria parasites in the mosquito vector is completed when the sporozoites infect the salivary gland and are ready to be injected into the vertebrate host. This paper describes the fine structure of the invasive process of mosquito salivary glands by malaria parasites. Plasmodium gallinaceum sporozoites start the invasion process by attaching to and crossing the basal lamina and then penetrating the host plasma membrane of the salivary cells. The penetration process appears to involve the for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
112
0

Year Published

1997
1997
2022
2022

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 118 publications
(115 citation statements)
references
References 23 publications
3
112
0
Order By: Relevance
“…A recent electron microscopic study demonstrates that salivary gland invasion by sporozoites is a multistep process involving sequential interac tions with the basal lamina and the plasma membrane of the target cell [20]. The first event in invasion is the adhesion of the sporozoite to the target cell.…”
Section: Discussionmentioning
confidence: 99%
“…A recent electron microscopic study demonstrates that salivary gland invasion by sporozoites is a multistep process involving sequential interac tions with the basal lamina and the plasma membrane of the target cell [20]. The first event in invasion is the adhesion of the sporozoite to the target cell.…”
Section: Discussionmentioning
confidence: 99%
“…Ultrastructural studies have shown that sporozoites invading salivary glands may encounter one receptor at the basal lamina of the salivary glands and another at the plasma membrane of the secretory cells (15). Other studies have indicated that the salivary gland components are highly glycosylated (2) and that specific lectins can inhibit sporozoite invasion of the salivary glands (3).…”
Section: Discussionmentioning
confidence: 99%
“…The sporozoites recognize the female-specific lobes of the salivary glands (14,15). Both the 29-kDa and 100-kDa salivary gland proteins are expressed on these lobes and fit the logical parameters we considered for a putative salivary gland receptor for sporozoites.…”
Section: Discussionmentioning
confidence: 99%
“…Although sporozoites are likely passively transported throughout the hemocoel, there is evidence that they specifically recognize the salivary glands through a receptor-mediated process [4][5][6][7]. Sporozoites breach the basal lamina and acinar gland cells and accumulate in the salivary duct [8]. When the infected mosquito takes another blood-meal, salivary gland sporozoites are injected into the avascular portion of the skin [9,10] where they start vigorous gliding locomotion in search of a capillary [11,12].…”
Section: Introductionmentioning
confidence: 99%